Seasonal variation in chemical attributes of Latosols in an area submitted to water stress in the Amazon - Guerreiro, Quêzia Leandro de Moura; Ruivo, Maria de Lourdes Pinheiro; Castro, Rosecélia Moreira Silva; Amarante, Cristine B.; Rodrigues, Hernani; Ferreira, Oberdan Oliveira (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
It is possible that the balance of the biosphere is modified by global changes of natural and/or anthropogenic origin. The aim of this research was to evaluate the seasonal variation in chemical attributes of soils in an Amazonian forest. Soil samples were taken in the rainy, transitional, and dry seasons in the ESECAFLOR experimental area where rainfall was excluded and in the Biodiversity Research Program (PPBio) area of the Caxiuanã National Forest (Pará, Brazil). The soil samples for chemical analyzes and soil humidity determination were collected at depths of 0-5, 5-10 and 10-20 cm with a soil auger. The highest nutrient levels were found in the PPBio area. Significant differences were found between areas except for magnesium and the base sum. There were significant differences in the ESECAFLOR area only for pH and base saturation and in the PPBio area only for sodium. There was also vertical variation in both areas. The area that underwent anthropic alteration (ESECAFLOR) presented lower concentrations for most of the studied nutrients, demonstrating an influence of reduced rainwater on the availability of key elements in the soil.
Keywords: Soil. Chemical attributes. Tropical forest